Refocusing health promotion for syphilis prevention: results of a case-control study of men who have sex with men on England's south coast. Issue 1 (3rd February 2006) - Imrie, J; Lambert, N; Mercer, C H; Copas, A J; Phillips, A; Dean, G; Watson, R; Fisher, M
Abstract : Background: Prevention interventions have had little impact on syphilis outbreaks among men who have sex with men (MSM) and diagnosis rates continue to rise rapidly. Detailed studies of the determinants of syphilis transmission are needed to inform new prevention interventions. Objective: To investigate factors associated with recent syphilis diagnosis and recommend strategies for improved prevention interventions. Methods: A case-control study of MSM attending genitourinary medicine (GUM) and HIV outpatient clinics. Cases were MSM testing positive for early syphilis, based on either laboratory or microscopy results, with those testing negative being controls. All participants completed the same anonymous questionnaire covering demographics, lifestyle, sexual behaviour, and sexual partnerships. Results: 50 cases and 108 controls returned questionnaires. Syphilis diagnosis was significantly associated with sexually transmitted infection history, recent recreational drug use, receptive anal sex practices, but not insertive ones, higher numbers of oral sex partners, but not specific oral sex practices. Overall, there were no differences between HIV positive and HIV negative/untested men in reporting of sexual behaviours or partnership combinations. The use of public sex settings (backrooms, saunas, "cruising grounds, " etc) was reported by 68% of all participants and not significantly associated with syphilis diagnosis. Conclusions: Many key behavioural and partnership risk factors for syphilis are also risk behaviours for HIV transmission and point to the need for integrated strategies that tackle the two infections together. Simplified procedures for syphilis screening should be available in GUM clinical settings, along with targeted community outreach prevention interventions.